If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(n+3)(2n-3)=0
We multiply parentheses ..
(+2n^2-3n+6n-9)=0
We get rid of parentheses
2n^2-3n+6n-9=0
We add all the numbers together, and all the variables
2n^2+3n-9=0
a = 2; b = 3; c = -9;
Δ = b2-4ac
Δ = 32-4·2·(-9)
Δ = 81
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{81}=9$$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(3)-9}{2*2}=\frac{-12}{4} =-3 $$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(3)+9}{2*2}=\frac{6}{4} =1+1/2 $
| 2(3y-1)=7y-4 | | 240=4m/2 | | 2x²-3=0 | | 180=10v/2 | | 3÷8=m÷64 | | x^2-6+4=-7x+6 | | -3(3+y)=15 | | 5=(y+4)=20+65 | | -2p-4=-14 | | 4(m+2)-2(m+4)=7 | | 3x4+-6x3+-72x2=0 | | 4(2x-3)=5x+7 | | 3x-(5x-6)=26 | | 7x-19=3(x-3) | | (5m+1)(6m+5)=0 | | 6x-8.5=2x+3.5 | | 2.x+23=772 | | 4(2x+5)-4x-4=36 | | 28-9b=4 | | -5(-2x-5)-x-1=−5(−2x−5)−x−1=-12 | | 7/6x=18 | | 10x−6=6+9x | | (D^5+14D^3+49D)y=0 | | 2c1=11 | | 2x-9=45.1 | | 4x+6=18+2xx= | | (x-2)(x^2-4)(x^2+16)=0 | | m/45=77/55 | | x-2(x-4)=3x-2(3-x | | 2/3a+1/4=5/12 | | 30=3(2x2x) | | 5(3+2x)=40 |